Sustainable Initiatives and Carbon Credit in the Context of the Maslow Pyramid (Journal of Management & Business, 2025)
The objective of this study is to analyze how different Brazilian companies are incorporating sustainable and innovative practices to meet self-actualization needs, as described in Maslow’s Hierarchy of Needs, applied to carbon credits. It seeks to understand how these practices not only contribute to mitigating climate change but also promote sustainable development and economic and environmental security. For this purpose, annual and sustainability reports of companies participating in the Brazilian Initiative for the Voluntary Carbon Market, coordinated by McKinsey & Company, were analyzed. The methodology involved the collection and analysis of data from these reports, categorizing sustainability and innovation practices according to the levels of Maslow’s Hierarchy of Needs. The main results show that companies have significantly invested in decarbonization and commercialization of carbon credits, with initiatives that meet physiological, safety, social, esteem, and self-actualization needs. These practices have positively impacted sustainable development and the economic and environmental security of Brazil.
Keywords: Carbon Credits; Maslow's Hierarchy of Needs; Economic Security; Brazilian Companies